The Malay law text - Mohamad Jajuli A. Rahman; Dewan Bahasa dan Pustaka (Kuala Lumpur Dewan Bahasa dan Pustaka, Ministry of Education, Malaysia, 1995)
Comments, transliteration, and translation of a law text in Jawi script: MS 2393, Sloane collection, British Museum.
Includes bibliographical references (p. 109-114) and index.
English and Malay.
Keywords: Islamic law -- Southeast Asia; Islamic law -- Malay Archipelago -- Sources